60th ANNIVERSARY AND WITH MANY MORE YEARS TO COME - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 8 May 2017 – This year marks the 60th anniversary of the establishment of diplomatic relations between Malaysia and Japan. Since then, bilateral relations have been strengthened through the implementation of the ‘Look East Policy’ then and now, it is the ‘Look West Policy’ for the Japanese to turn its attention to Malaysia.